Effectiveness of a Culturally-Tailored Smoking Cessation Intervention for Arab-American Men - Haddad, Linda G. (Int J Environ Res Public Health, 2017)
To date, no smoking cessation programs are available for Arab American (ARA) men, who are a vulnerable population with high rates of smoking. Thus, the primary aim of this one group pre-test/post-test study was to assess the effectiveness of Sehatack—a culturally and linguistically tailored smoking cessation program for ARA men. The study sample was 79 ARA men with a mean age of 43 years who smoked between 5 and 40 cigarettes (mean = 19.75, SD = 9.1) per day (98.7%). All of the participants reported more interest in smoking cessation post-intervention and many of the participants in the baseline (38.5%) and post-intervention phases (47.7%) wanted to quit smoking ”very much”. For daily smokers who completed the smoking cessation program, the median number of cigarettes smoked daily was significantly lower than those in the post-intervention phase (Z = −6.915, p < 0.001). Results of this preliminary study indicate that: (a) Sehatack may be a promising way for ARA men to quit smoking, and (b) culturally relevant smoking cessation counselors can be trained to recruit and retain ARA smokers in an intensive group smoking cessation program. Strengths of this study were community engagement and rapport between three faith organizations and the University of Florida College of Nursing. However, a larger trial is needed to address study limitations and to confirm benefits in this population.